A study of earning quality among MESDAQ listed companies - Siti Nor Junita, Mohd Radzi; Suraiya, Ibrahim; Md. Aminul Islam (Universiti Malaysia Perlis (UniMAP), 2011)
The 2nd International Conference on the Roles of Humanities and Social Science in Engineering (ICoHSE 2010) organized by Universiti Malaysia Perlis (UniMAP), 12th - 14th November 2010 at Bayview Beach Resort, Penang, Malaysia.